Effect of Benson Relaxation and Warm Foot Soak Combination on Blood Glucose Regulation in Type 2 Diabetes Mellitus Patients: Case Report - Fitriyani, Novia; Rahayu, Henik Tri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Type 2 diabetes mellitus (DM type 2) is a chronic metabolic disorder marked by elevated blood glucose due to insulin resistance and impaired insulin secretion. Its prevalence continues to rise worldwide, including in Indonesia. Psychological stress is known to worsen glycemic control by activating the sympathetic nervous system and increasing cortisol levels, which can cause fluctuations in blood glucose. This case report aims to describe the effect of combining Benson relaxation techniques with warm foot soaking on blood glucose regulation in a type 2 DM patient. The subject was Mrs. M, a 52-year-old woman diagnosed with type 2 DM. The intervention was conducted for seven consecutive days and consisted of daily Benson relaxation followed by warm foot soaking for 15–20 minutes. Blood glucose levels were measured before and after each session using a glucometer and analyzed descriptively. After seven days, the patient’s blood glucose level decreased from 248 mg/dL to 186 mg/dL. She also reported improved relaxation, better sleep quality, reduced anxiety, and decreased fatigue. These findings suggest that Benson relaxation helps activate the parasympathetic response and reduce stress hormones, while warm foot soaking supports improved circulation and metabolic processes. In conclusion, the combination of Benson relaxation and warm foot soaking is a simple, safe, and effective complementary therapy to support blood glucose regulation in type 2 DM patients. This intervention can be integrated into self-care routines and community nursing practice as part of evidence-based non-pharmacological management.